2016
DOI: 10.1111/evo.13020
|View full text |Cite
|
Sign up to set email alerts
|

The mutational structure of metabolism inCaenorhabditis elegans

Abstract: A properly functioning organism must maintain metabolic homeostasis. Deleterious mutations degrade organismal function, presumably at least in part via effects on metabolic function. Here we present an initial investigation into the mutational structure of the Caenorhabditis elegans metabolome by means of a mutation accumulation experiment. We find that pool sizes of 29 metabolites vary greatly in their vulnerability to mutation, both in terms of the rate of accumulation of genetic variance (the mutational var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
33
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 57 publications
4
33
2
Order By: Relevance
“…Although we lacked the power to fully explore the affect of mutation on the distribution of variation across phenotypic space we note that the major axis of relative difference in variance between control and mutant males (d 1 ) reflected variation in multiple body shape traits (Table 1). Uneven distribution of mutational variance across phenotypic space has been reported previously for morphology, gene expression, locomotor performance, and metabolites (Houle and Fierst 2013;Latimer et al 2014;McGuigan et al 2014;Davies et al 2016), suggesting that mutation might typically bias the distribution of variation available to evolution.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Although we lacked the power to fully explore the affect of mutation on the distribution of variation across phenotypic space we note that the major axis of relative difference in variance between control and mutant males (d 1 ) reflected variation in multiple body shape traits (Table 1). Uneven distribution of mutational variance across phenotypic space has been reported previously for morphology, gene expression, locomotor performance, and metabolites (Houle and Fierst 2013;Latimer et al 2014;McGuigan et al 2014;Davies et al 2016), suggesting that mutation might typically bias the distribution of variation available to evolution.…”
Section: Discussionmentioning
confidence: 61%
“…In contrast to the expectation of bias for fitness, traits not closely associated with fitness are predicted to show no change in population mean under mutation (Johnson and Barton 2005). Again, available evidence is mixed; some studies reported no mutational effects on trait mean of nonfitness traits (Santiago et al 1992;Camara et al 2000;Houle and Fierst 2013;Stearns and Fenster 2016), while other studies reported mutational bias (Camara et al 2000;McGuigan and Blows 2013;Davies et al 2016). The potential for mutation to shift population trait means requires further investigation across different types of traits and taxa to determine whether mutational biases on trait mean might be common, and what types of traits might typically be affected.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…More recently, DAVIES et al (2016) examined the changes in metabolite concentration 74 for 29 metabolites in a set of C. elegans MA lines that had undergone ~250 generations of 75 evolution under minimal selection and found that metabolites vary considerably in their 76 response to spontaneous mutation, as quantified by the change in mean metabolite 77 concentration (ΔM) and by the mutational (co)variance. Associations between mutational 78 correlations between pairs of metabolites (rM, presumably the result of pleiotropy) and proximity 79 of the metabolites in the global metabolic network were, on average, positive but weak 80 (JOHNSON et al 2018).…”
Section: Introduction 44mentioning
confidence: 99%